2016
DOI: 10.1063/1.4953075
|View full text |Cite
|
Sign up to set email alerts
|

Generation of topologically diverse acoustic vortex beams using a compact metamaterial aperture

Abstract: Vortex waves, which carry orbital angular momentum, have found use in a range of fields from quantum communications to particle manipulation. Due to their widespread influence, significant attention has been paid to the methods by which vortex waves are generated. For example, active phased arrays generate diverse vortex modes at the cost of electronic complexity and power consumption [1][2][3][4] . Conversely, analog apertures, such as spiral phase plates 1,5 , metasurfaces 6 , and gratings 7 require separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…For acoustics, the underwater propagation of vortex beams with single topological charge was demonstrated with active phase arrays (20,21). Passive acoustic phase modulation structures were proposed to generate single-charge vortex beams (22)(23)(24)(25). These acoustic vortex beams were used to develop acoustic tweezers, and screwdrivers for particle trapping, levitation, and manipulations (26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…For acoustics, the underwater propagation of vortex beams with single topological charge was demonstrated with active phase arrays (20,21). Passive acoustic phase modulation structures were proposed to generate single-charge vortex beams (22)(23)(24)(25). These acoustic vortex beams were used to develop acoustic tweezers, and screwdrivers for particle trapping, levitation, and manipulations (26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…In this case, the waveguide is curved into an annulus shape, with the sound entering into the annulus from a source, propagating around the circular path, and then exiting the annulus, similar to the arrangement examined in Ref. 61. Although the physical structure consists of circular annulus, a spacer at θ = 0 prevents the interaction of sound within the waveguide between the signals entering and exiting the annulus.…”
Section: Acoustic Vortex Wave Antennamentioning
confidence: 99%
“…While extensively studied for microwaves 46,47 and more recently using metamaterials [48][49][50][51][52][53][54][55][56] , optical LWAs present various challenges which are the subject of ongoing research 47,57 . In addition to electromagnetic (EM) waves, acoustic LWAs have recently been demonstrated to generate one-dimensional (1D) axisymmetric planar acoustic waves 58,59 , two-dimensional (2D) planar waves 60 and topologically diverse circular acoustic vortex waves 61 . A detailed theoretical formulation for an acoustic antenna utilizing these recent advances with acoustic leaky-wave antennas is presented in Sec.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has also demonstrated the manipulation of beams for particle trapping [23,24] and boosting communication efficiency [25,26] with acoustic angular momentum. Passive generation of wave fields with non-zero angular momentum is typically imple-mented by leaky wave antennas or metasurfaces based on generalized Snell's law (GSL) [27,28] for acoustic waves and inhomogeneous anisotropic media [29], spatial light modulator or spiral phase plates [30,31] for electromagnetic waves. However, the recent advances in metasurfaces for perfect wavefront manipulation show that if only the transmission phase profile is controlled, parasitic scattering inevitably appears, which reduces the efficiency, or even cause the failure to the structures, especially for large angular momentum.…”
Section: Introductionmentioning
confidence: 99%